EFEKTIVITAS E-LEARNING BERBASIS GOOGLE MEET DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Primadi, Rizky Setia (Universitas Tanjungpura, 2024)
this study aims to determine: 1) Student learning results without using Google Meet. 2) Student learning outcomes by using Google Meet 3) Effectiveness of Google Meet -Based Learning in Improving Learning Outcomes. The research method used is experimentation. Class XI IPS 3 and 4 students became a sample with a total of 63 students. This data collecting techniques using learning outcomes test techniques, then analyzed with a quantitative approach. The results showed: 1.) Learning outcomes from class XI IPS 3 with WhatsApp Group are known the lowest value of 61 and test highest value is 100 with an average value of 82.87. And of the 31 students only 7 who got scores below KKM 2.) Learning outcomes from class XI IPS 4 with Google Meet are known to the lowest value of 72 and test highest score is 100 with an average value of 87.06, and of 32 students only 2 who got Value below KKM.3). Judging from the Effect Size test results, which is 0.15 which is low with a percentage of 54%. results of the Independent Sample t-test are known to the value of Sig.(2-tailed) in the equal variances assumed section, namely 0.0670.05, which means that there is no significant difference between the experimental class and the control class. It can be concluded that in this study, learning based on Google Meet was not effective.